The soil available P, Plant P uptake, Growth, and yield of corn in Regosol Soil Treated with Ela Sago Compost and SP-36 Fertilizer - Kaya, Elizabeth; Putinella, June Annethe; Puturuhu, Ferad (JOURNAL OF TROPICAL SOILS, 2025)
The research examined the effect of ela sago compost on the soil chemical properties, growth, P-uptake, and yields of corn plants (Zea mays L) in Regosol soils. A randomized block design with a 2 x 4 factorial treatment was applied. The first factor was ela sago compost (B) with three dose levels: B0 = 0-Mg ha-1, B1 = 10-Mg ha-1, and B2 = 20-Mg ha-1. The second factor was SP-36 (P) fertilizer with four dose levels: P0 = 0 kg P ha-1, P1 = 60 kg P ha-1, P2 = 120 kg P ha-1, and P3 = 180 kg P ha-1. This research shows that either ela sago compost or SP-36 fertilizer can increase the soil reaction (pH). Applying sago palm compost and SP-36 fertilizer increases soil available P from 17.33 to 60.67 ppm. Applying sago palm compost and SP-36 fertilizer increases plant P-uptake from 0.18 to 0.40 %, plant height from 135.60 to 189.67 cm, and stem diameter from 1.86 to 3.44 cm, and corn yield (dry weight of 1000 seeds) from 266.60 to 390.57 g.